(untitled) (Research, Society and Development, 2022)
This study aimed to evaluate the knowledge of students from the Federal University of Pernambuco at the Academic Center of Vitória (UFPE/CAV) about the new Coronavirus and COVID-19. The present study presented a cross-sectional and quantitative aspect, where the inclusion criteria were the students of UFPE/CAV over 18 years of age and the exclusion criterion were students from other university and professors at UFPE/CAV. The composition of the questionnaires was based on several questions that could be related to the COVID-19 pandemic, obtaining 6 variables with 29 questions in total. The questionnaire was published through Google Forms on Facebook, Instagram, WhatsApp and E-mail, it contained the TCLE for the consent of the survey of participants. From the results obtained it was possible to notice that most of the students answered the questions proposed in the research. It was also noticeable statistical differences in the answers of some questions between nursing courses, biological sciences and collective health. Moreover, despite demonstrating a lot of knowledge about the issues related to COVID-19, students obtain some knowledge deficit in some questions, especially on aspects related to consequences of COVID-19, so there is a need for reinforcement in the dissemination and communication of true information. Moreover, this research can help decision-making for coping strategies of the new Coronavirus, both for educational institutions and for society.